ROH KUDUS SEBAGAI “METERAI－JAMINAN” DALAM EFESUS 1:13-14 SERTA IMPLIKASINYA BAGI SOTERIOLOGI KRISTEN - Bruno Ikun Anen; Mozes Lawalata (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2026)
The Holy Spirit is a divine person who plays a vital role in all biblical evidence. Since creation, the Spirit of God has been present and actively working in shaping and sustaining creation according to God's will (Genesis 1:2). In the Old Testament, the Spirit of God empowered judges, prophets, and the chosen people to carry out their duties in the plan of salvation, while also providing the basis for the eschatological hope of the renewal of humanity through the outpouring of the Spirit. In the New Testament, the work of the Holy Spirit is increasingly evident through the life and ministry of Jesus Christ, from his birth and baptism to his ministry as the fulfillment of messianic prophecy. In Pauline theology, the Holy Spirit is the core experience of salvation because through the Spirit believers are renewed, freed from the power of sin, and live in fellowship with God. Ephesians 1:13–14 is a key text that affirms that believers are